Cable current-carrying status analysis and early fault warning method based on temperature information. (17th March 2023) - Yang, Hanrui; Lv, Huanhuan; Zhang, Jingwei; Huang, Weiliang; Xu, Shibo; Jiao, Shengxi
Abstract: Long-term operation of cables and equipment under abnormal currents can cause insulation aging and reduce the service life of the equipment. Identifying the current-carrying status accurately and early detection of potential failures of power cables is particularly significant for ensuring the operation of power equipment safely and economically. This paper proposed a method for detecting the current-carrying status of power cables and an early fault warning based on temperature information. Based on the theoretical basis of the relationship between temperature and current. According to IEC 61000-3-7 and IEC 60038 standards, the current-carrying state evaluation method is analyzed and given, and the early fault warning model is established. Finally, the paper takes the cable connector and the lightning arrester in the power ring network cabinet as an example to verify the method's feasibility. It shows that the characteristic information of the relative temperature variation curves under different current carrying states significantly differs. Includes the slope of hour 9, the slope of hour 2, and the maximum. Then the total duration under abnormal current operation is calculated, and the early warning of faults can realize.